2010
DOI: 10.1007/s11033-010-0179-y
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of adipokines in osteoarthritis: a narrative review

Abstract: Osteoarthritis (OA) is a most common multifactorial degenerative joint disease in elderly individuals. OA is affecting severely the quality of life of patients, while the causes of OA are not completely understood. Age, obesity, the female sex, and previous injury are considered as significant risk factors. Recently, increased levels of adipokines which are mainly produced by adipocytes have been detected in patients with osteoarthritis. Moreover, studies on different adipokines all reveal that they have playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 80 publications
2
52
0
1
Order By: Relevance
“…Considerably strong and growing evidence supports the important role of various adipokines in OA (Hu et al 2011;Conde et al 2011). Adipokines were also viewed as a potential metabolic factor which link obesity to OA (Gabay and Berenbaum 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerably strong and growing evidence supports the important role of various adipokines in OA (Hu et al 2011;Conde et al 2011). Adipokines were also viewed as a potential metabolic factor which link obesity to OA (Gabay and Berenbaum 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin has proinflammatory and immunomodulating functions (Sun et al 2013) and manifested a pro-degradative effect in cartilage by i n c r e a s i n g t h e s y n t h e s i s o f M M P -3 , M M P -1 3 , thrombospondin motifs (ADAMTS)-4, and ADAMTS-5 (Gosset et al 2008;Hu et al 2011;Laiguillon et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The role of adiponectin played in the inflammatory process is not completely elucidated. It was suggested that it affects IL-1β, IL-6, MMP-13 [39], MMP-1, MMP-3, NO [38], and MMP-9 secretion [40].…”
Section: Adiponectinmentioning
confidence: 99%
“…Accordingly, reduced plasma levels of adiponectin are reported to be associated with an increased risk in developing insulin resistance, type 2 diabetes mellitus (T2DM), obesity, metabolic syndrome, and even osteoarthritis (Kadowaki et al, 2006;Matsuzawa et al, 2004;Weyer et al, 2001;Daimon et al, 2003;Hu et al, 2011). The protective effect of adiponectin against these metabolic phenotypes may involve the suppression of hepatic gluconeogenesis, stimulation of fatty acid oxidation in the liver, stimulation of fatty acid oxidation and glucose uptake in the muscle and the stimulation of insulin secretion (Rabe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%